Corticosteroids alter kidney development and increase glomerular filtration rate in larval zebrafish (Danio rerio) - Heigwer, Jana; Steenbergen, Petrus J.; Gehrig, Jochen; Westhoff, Jens (Toxicological sciences, 2024)
Pharmaceutical drugs and other chemicals can impact organogenesis, either during pregnancy or by postnatal exposure of very preterm infants. Corticosteroids are administered to pregnant women at risk of preterm delivery in order to reduce neonatal morbidity and mortality. In addition, high-dose corticosteroid exposure of very preterm infants regularly serves to maintain blood pressure and to prevent and treat bronchopulmonary dysplasia, a form of chronic lung disease in prematurely born infants. Despite clinical benefits, there is increasing evidence of corticosteroid-mediated short- and long-term detrimental developmental effects, especially in the kidney. Here, we performed a detailed morphological and functional analysis of corticosteroid-mediated effects on pronephros development in larval zebrafish. About 24-h postfertilization (hpf) transgenic Tg(wt1b: EGFP) zebrafish larvae were exposed to a set of natural and synthetic corticosteroids (hydrocortisone, dexamethasone, 6α-methylprednisolone, betamethasone, prednisolone, fludrocortisone, 11-deoxycorticosterone) with varying glucocorticoid and mineralocorticoid potency for 24 h at different concentrations. A semiautomated, multiparametric in vivo workflow enabled simultaneous assessment of kidney morphology, renal FITC-inulin clearance, and heart rate within the same larva. All corticosteroids exerted significant morphological and functional effects on pronephros development, including a significant hypertrophy of the pronephric glomeruli as well as dose-dependent increases in FITC-inulin clearance as a marker of glomerular filtration rate. In conclusion, the present study demonstrates a significant impact of corticosteroid exposure on kidney development and function in larval zebrafish. Hence, these studies underline that corticosteroid exposure of the fetus and the preterm neonate should be carefully considered due to potential short- and long-term harm to the kidney.